Drawing up maps of infertile soil plots using geographic information systems. Issue 4 (1st October 2016) - Gaudėšius, Rimvydas
Abstract: There are quite a lot of unused plots of lands that are suitable for agriculture or other business in the territory of Lithuania. This has happened because of various social, natural and economic reasons. Scientists emphasize that all intensity of agricultural production is determined by different conditions of development of agricultural activities. Productivity of soil is highly significant in this case. Big farmers control vast territories in which natural conditions are different. Some farmers engage in one type of activities in their farms, whereas others develop different business. Using the territory used for agriculture to engage in different activities is more efficient economically because different crops need different conditions to grow; therefore, it is possible to obtain higher economic efficiency taking into account the characteristics of soil. Taking into account the relevance of such a map in practice, it was decided to try to draw it up using geographic information systems. The biggest problem while performing this task is the fact that initial information is saved in different formats. The article also describes the capacities of software. It is noteworthy that the situation is analyzed in respect of drawing up a map of individual holdings not a mass map of unproductive land. The article is more of practical nature; therefore, the results reflect program capacities and theoretical ideas more that could be useful in business and expand the capabilities of land management officers' activities.